SPECULATIVE BUBBLES AND MONETARY POLICY : a theory based on japanese experience. - OTAKI, MASAYUKI (LEXINGTON Books, 2018)
This book works at the intersection of economic theory history. It presents a Keynesian theory with a rigorous dynamic microeconomic foundation that entirely differs from new Keynesian theory and applies it to the Japanese economic history from the 1980s to 2010s.